Transversal and Professional Skills Self-Efficacy Scale: Cultural Adaptation and Evidence of Validity - Audibert, Alyane (2020)
Today, the preparation for working life and lifelong career management is becoming increasingly demanding challenges. Hence, in recent years, transversal competences have become more important. The aim of this paper is to present the adaptation study to the Brazilian context of the Transversal and Professional Skills Self-Efficacy Scale (TPS-SE), originally developed in Portugal. The sample consists of 658 Brazilians, 85.7% women. Exploratory and confirmatory factor analysis procedures were performed, and the final model presented satisfactory adjustment ratios, offering an alternative version with a general factor, and confirming the three-factor structure of the original scale, which assesses confidence in the ability to perform (1) personal and interpersonal skills in the workplace, (2) complex personal skills, and (3) transversal technical skills. It can be concluded that TPS-SE_Br can be used in intervention and research contexts, either in the form of general indicators, clustered in dimensions or in an individual item analysis.